British Parliamentary Debate as a Strategy to Assist Eleventh Graders’ Speaking Skills on Using Agreement and Disagreement Expressions - Fathur Muhammad (Retain: Journal of Research in English Language Teaching, 2025)
Abstrak Tujuan dari penelitian ini adalah untuk menyelidiki tanggapan dan tantangan yang dihadapi siswa setelah menggunakan debat sebagai strategi untuk membantu keterampilan berbicara siswa pada materi persetujuan dan ketidaksetujuan. Penelitian ini menggunakan metode kualitatif dengan subjek siswa kelas XI di sebuah sekolah menengah swasta di Sampang, yang terdiri dari 11 siswa. Data dikumpulkan dari data primer melalui wawancara dan dianalisis menggunakan model analisis Miles dan Huberman. Wawancara semi-terstruktur dilakukan untuk menjawab pertanyaan penelitian pertama dan kedua. Hasil penelitian ini menunjukkan bahwa penggunaan debat sebagai strategi membantu keterampilan berbicara siswa pada materi persetujuan dan ketidaksetujuan dalam berbagai aspek seperti kelancaran, perolehan kosakata, kepercayaan diri, dan berpikir kritis. Hasil tanggapan siswa juga menunjukkan bahwa terdapat beberapa tantangan yang dihadapi siswa selama debat, seperti kekurangan kosakata, manajemen waktu, pengendalian emosi, berpikir dan berbicara dalam bahasa Inggris secara bersamaan, serta kurangnya pemahaman mendalam terhadap topik. Abstract The purpose of this study is to investigate the students’ responses and challenges after using debate as a strategy to assist students speaking skills on agreement and disagreement material. This study employed a qualitative method with the subjects of eleventh graders at private high school in Sampang, consisting of 11 students. The data was collected from primary data through interviews and analyzed it by using Miles and Huberman analysis model. Semi-structured interviews were conducted to answer the first and the second research question. The results of this study indicate that the use of debate as a strategy assisted students' speaking skills on agreement and disagreement material in various aspects such as fluency, vocabulary acquisition, confidence, and critical thinking. The result of students’ responses also shows that there are several challenges faced by the students during debate such as; lack of vocabulary, time management, handling emotions, thinking and speaking in English simultaneously, and lack of in-depth understanding of the topic.